Burnout pada mahasiswa praktikum alat tes psikologi: Bagaimana peranan strategi coping - Cici Indah Cahyawati; Bawinda Sri Lestari (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between coping strategies with burnout in practicum students. Psychological tests. The research subjects were psychology faculty students University of 17 August 1945 Surabaya who took the practicum of 12 psychological test instruments with a sample of 70 people taken by random technique. Data collection used a coping strategy scale developed by the researcher and a burnout scale, using the Likert model. Data analysis technique using the person product moment correlation test, with the correlation (r) between the variable coping strategy and burnout of 0.173 with a p value = 0.153 (p> 0.05) which means that there is no relationship between coping strategies with burnout in practicum students of psychological test equipment. Keywords: Burnout; coping strategies; practicum students